2007
DOI: 10.1159/000101778
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Endothelium-Derived Hyperpolarizing Factor Is Augmented in Monocrotaline-Induced Pulmonary Hypertension of Rat Lungs

Abstract: The mechanism of endothelium-dependent vasodilator signaling involves three components such as nitric oxide, prostacyclin, and endothelium-derived hyperpolarizing factor (EDHF). Although EDHF is distinct from nitric oxide and prostacyclin, it requires activation of Ca2+-sensitive K+ channels (KCa) and cytochrome P450 metabolites. However, the physiological role of EDHF in the pulmonary circulation is unclear. Thus, we tested if EDHF would regulate vascular tone in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 97 publications
1
8
1
Order By: Relevance
“…These findings suggest that EETs do not contribute to endothelium-dependent NS309 relaxation in rat pulmonary arteries. Recent studies have reported that cytochrome P450 epoxygenase derivatives are involved in hypoxic vasoconstriction (39), and the present results do not exclude EETs contributing to endothelium-dependent relaxations in arteries from animals with pulmonary hypertension (36). K ϩ (5-22.5 mM) induces relaxation through activation of Na ϩ -K ϩ -ATPase and K ir channels in the vascular smooth muscle (14), and it was suggested that K ϩ ions released from IK Ca and SK Ca channels in the endothelium accumulate in the intercellular space and thereby activate K ir channels and Na ϩ -K ϩ -ATPase leading to EDHF-type relaxation in rat mesenteric arteries (14).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings suggest that EETs do not contribute to endothelium-dependent NS309 relaxation in rat pulmonary arteries. Recent studies have reported that cytochrome P450 epoxygenase derivatives are involved in hypoxic vasoconstriction (39), and the present results do not exclude EETs contributing to endothelium-dependent relaxations in arteries from animals with pulmonary hypertension (36). K ϩ (5-22.5 mM) induces relaxation through activation of Na ϩ -K ϩ -ATPase and K ir channels in the vascular smooth muscle (14), and it was suggested that K ϩ ions released from IK Ca and SK Ca channels in the endothelium accumulate in the intercellular space and thereby activate K ir channels and Na ϩ -K ϩ -ATPase leading to EDHF-type relaxation in rat mesenteric arteries (14).…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, it is plausible to suggest that in humans, some mechanisms may exist to compensate for the deficiency of BH4 in the pulmonary vessels, as was seen in the systemic endothelium that do not exist in the mice. For example, other endothelial mediators such as endothelium-derived hyperpolarizing factor 30 or prostacyclins 31 may have been upregulated in the pulmonary as well as the systemic vasculature. Similarly, downregulation of endothelins 32 or a reduction in sympathetic response may have reduced the physiological antagonism of the pulmonary arterial bed.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell adhesion molecules play a pivotal role in the recruitment and binding of inflammatory cells to the vascular endothelium during the development of vascular disease. Since several reports suggested that elevated VCAM-1 levels reflect the impairment of endothelial function (26), VCAM-1 has been regarded as a marker of endothelial dysfunction. In this study, we demonstrated the augmentation of lung VCAM-1 expression and plasma ET-1 levels, and reduction of lung eNOS expression, suggesting endothelial dysfunction characterized by downregulation of eNOS expression and upregulation of ET-1 levels in the PE rat.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although vascular endothelial dysfunction may exist during the development of vascular disease, there are no studies that have determined the contribution of pulmonary vascular endothelial dysfunction in the pathogenesis of PE. We thus investigated the expression of vascular cell adhesion molecule-1 (VCAM-1) and endothelial nitric oxide synthase (eNOS) to evaluate the pulmonary vascular endothelial dysfunction in the PE rats (22,24,26). We also tested whether Rho kinase inhibitor is capable of attenuating the degree of pulmonary hypertension and hypoxemia in the PE rats in vivo.…”
mentioning
confidence: 99%